Preventable Risk Factors for Non-Communicable Diseases in Urban Slum of Mumbai: A Prevalence Study Using Who Steps Approach - Kalpak S Kadarkar; Gajanan D Velhal; Shraddha R Tiwari (Medsci Publications, 2016)
Context: India is experiencing a rapid health transition with a rising burden of non-communicable diseases causing significant morbidity and mortality, both in urban and rural population. The STEPwise approach is WHO-recommended framework for NCD surveillance. Study was conducted to assess the prevalence of risk factors of NCDs among residents of urban slum. Methods and Material: Using WHO STEPwise approach a cross-sectional study was carried out among participants of 25-64 years age group in the slum. Information on behavioural and physiological risk factors of non-communicable diseases was obtained through standardized protocol. Results: Smoking prevalence was high among men (27.5%) compared to 2% in women. The use of smokeless tobacco was reported by 38.5% of men and 9.5% of women. The prevalence of raised blood pressure was slightly more in males (40.5%) as compared to females (37.5%). Mean BMIs and prevalence of obesity was nearly same among men and women. Women were less physically active when compared to men. Fruits and vegetable consumption was low among both men and women. Conclusions: The high prevalence of risk factors in urban slum alarms the likelihood of a high future burden of diseases highlights need for different interventions and approaches for prevention of risk factors of non-communicable diseases.